2017
DOI: 10.2196/jmir.7310
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen Challenges in Establishing a Multidisciplinary Research Program on eHealth Research in a University Setting: A Case Study

Abstract: BackgroundU-CARE is a multidisciplinary eHealth research program that involves the disciplines of caring science, clinical psychology, health economics, information systems, and medical science. It was set up from scratch in a university setting in 2010, funded by a governmental initiative. While establishing the research program, many challenges were faced. Systematic documentation of experiences from establishing new research environments is scarce.ObjectiveThe aim of this paper was to describe the challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 22 publications
(27 reference statements)
0
46
0
Order By: Relevance
“…Overall, the Fig. 2 Framework of the context-mechanism-outcome onfiguration in cross-disciplinary health policy and systems research literature identified cross-disciplinarity as a distinctive approach whose context, including the scope of the research problem [20-22, 24, 52, 54, 64, 65], purpose of investigation [13,14,23,53,55,56,[66][67][68][69] and study setting [13,24,55,60,66,67,[70][71][72] differ from monodisciplinary approaches. We found that these context-dependent characteristics proceed to define the mechanisms and outcomes of cross-disciplinarity [13, 20-23, 52-57, 59, 60, 64, 67, 70, 73, 74].…”
Section: Cmo Configuration In Cross-disciplinary Hpsrmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, the Fig. 2 Framework of the context-mechanism-outcome onfiguration in cross-disciplinary health policy and systems research literature identified cross-disciplinarity as a distinctive approach whose context, including the scope of the research problem [20-22, 24, 52, 54, 64, 65], purpose of investigation [13,14,23,53,55,56,[66][67][68][69] and study setting [13,24,55,60,66,67,[70][71][72] differ from monodisciplinary approaches. We found that these context-dependent characteristics proceed to define the mechanisms and outcomes of cross-disciplinarity [13, 20-23, 52-57, 59, 60, 64, 67, 70, 73, 74].…”
Section: Cmo Configuration In Cross-disciplinary Hpsrmentioning
confidence: 99%
“…However, depending on the degree of cross-disciplinary integration, the research questions may differ across the involved disciplines (multidisciplinary health policy and systems research (MDHPSR)), may be shared between disciplines or have been mutually agreed upon (interdisciplinary health policy and systems research (IDHPSR) and transdisciplinary health policy and systems research (TDHPSR)). Some of the articles argue that combinations of findings from different monodisciplinary studies about a common health problem, which were not conducted in a predetermined •Co-design, co-investigation and cocreation limited to participating disciplines [22,57,74] •Philosophy of transient and intermittent conceptual, theoretical and methodological integration [55,75] •Focuses on explicit exchange of perspectives, concepts and methods [68,74], reciprocal discipline-specific action [54,60] •Integration traverse stakeholder, disciplinary, organisational and professional boundaries [20,53,59,67] •Formative scientific team [20,52,77] •Co-design, co-investigation and co-creation over disciplinary limits [20,52,67,74] •Philosophy of flexibility and ongoing integration in response to new information about the problem [20,28,74] •Reflects robust systematic interplay between research stakeholders (academic and nonacademic) and elements (design, data collection and analysis) of the research [20,76,78] Outcome •More basic than action-oriented output [13,75,79] •Output is the sum of individual evaluations [21,23,70] •Diverse perspectives to the topic being studied [13,21,…”
Section: Differences In Degrees Of Cross-disciplinary Integration In mentioning
confidence: 99%
See 2 more Smart Citations
“…Multidisciplinary collaboration, usually as a result of effective communication from experts of different career backgrounds, has reached to solve complex problems and create innovative products [46]. However, in a multidisciplinary environment, professionals may lack a basic common ground to communicate effectively (shared vocabulary and/or theoretical background), making it difficult to get a fully productive team [18]. Furthermore, understanding multidisciplinary domains allows to enable "productive and meaningful communication", and it is especially important when developing software, since a great effort is invested during requirements elicitation [25].…”
Section: Introductionmentioning
confidence: 99%